2021
DOI: 10.1159/000516881
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Bisphenol A Exposure and Early Childhood Behavior and Cognitive Function: A Chinese Birth Cohort Study

Abstract: <b><i>Introduction:</i></b> Biomonitoring of bisphenol A (BPA) in human blood is still scarce, although already noticeable. We aimed to examine the associations between prenatal serum BPA concentrations and behavior and cognitive function in preschool children. <b><i>Methods:</i></b> A total of 1,782 mother-child pairs with complete demographic information, blood samples, and psychological measurements were included from the China-Anhui Birth Cohort (C-ABCS). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…This is the first study that compared BPA levels between NCF and MCI participants. Previous studies that assessed the effect of BPA on cognition focused on the assessment of the impact of maternal exposure on foetus neurodevelopment or evaluated the effect of BPA exposure in children [22,50,51]. Braun et al [51] observed that prenatal BPA exposure had a more negative effect on cognitive function in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first study that compared BPA levels between NCF and MCI participants. Previous studies that assessed the effect of BPA on cognition focused on the assessment of the impact of maternal exposure on foetus neurodevelopment or evaluated the effect of BPA exposure in children [22,50,51]. Braun et al [51] observed that prenatal BPA exposure had a more negative effect on cognitive function in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Rodríguez-Carrillo et al [50] showed that BPA concentrations standardised to creatinine levels were associated with a higher risk of poorer working memory scores in school-age boys. Huang et al [22] discovered the different effects of maternal BPA exposure in girls and boys. Higher BPA levels in girls were associated with enhanced dangers of self-control inhibition, developing metacognition issues, behavioural challenges, difficulties in peer relationships, elevated total difficulties score, and increased impact factor score, whereas higher prenatal BPA levels in boys increased the risk of behavioural problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have shown that pre-and postnatal BPA exposure may increase neurobehavioral problems such as anxiety, depression, self-control issues, metacognitive dysfunction, aggression, emotional dysregulation, impaired peer relationships, social-communication disorders, and internalizing and externalizing problems in children. 140,143,[145][146][147][148][149][150][151] Although BPA exposure has potential adverse effects on children's intelligence and behavioral development, the results of these studies differed according to child sex and age. 143) Previous studies reported epidemiological evidence of an association between maternal BPA exposure and ASD.…”
Section: ) Bisphenol Amentioning
confidence: 99%
“…As a result, boys with the highest prenatal BPA concentrations showed an increase in conduct problems, while girls had behavioural and relationship problems. Therefore, high prenatal BPA concentrations have been shown to have a relationship with increased ADHD (Huang et al 2022b ). This association was also analysed in uterus exposure but no associations between BPA exposure and ADHD were observed (Hansen et al 2021 ).…”
Section: Effects Of Bpa On Humansmentioning
confidence: 99%